Adaptive Mediation and Conflict Resolution Peace-making in Colombia, Mozambique, the Philippines, and Syria - de Coning, Cedric; Muto, Ako; Saraiva, Rui (Sustainable Development Goals Series,, 2022)
'Books about liberal peacebuilding's shortcomings rarely go beyond platitudes of inclusion, local ownership, and flexibility. This book grapples seriously with what it would mean to put these principles into grounded practice in the real world of peace mediation and conflict resolution. Adaptive mediation means that the role of internationals is to accompany self-organized home-grown peace processes and to protect them from interference.' -Thania Paffenholz, Executive Director, Inclusive Peace, Switzerland 'This book demonstrates that respect for local realities is paramount for sustainable peace because each conflict is different. The argument also underwrites the recent experiences in Afghanistan. The book would be of value to those engaged in peace efforts as well as in post-conflict reconstruction.' -Tadamichi Yamamoto, Visiting Professor, Doshisha University, Japan, and Former Special Representative of the United Nations Secretary-General for Afghanistan and Head of the United Nations Assistance Mission in Afghanistan 'This book is a theoretically groundbreaking and empirically rich study on adaptive mediation. It is a must-read for scholars and students of peace and conflict research, as well as for peace practitioners interested in how peace mediation practices can better recognise the complexity of societies and conflict realities, redefine the role of the mediator, and address the demands of locally owned inclusive peace processes.' -Marko Lehti, Deputy Director of Tampere Peace Research Institute (TAPRI), Finland This open access book introduces adaptive mediation as an alternative approach that enables mediators to go beyond determined-design models of mediation. Adaptive mediation is grounded in complexity theory, and is specifically designed to cope with highly dynamic conflict situations characterized by uncertainty. It is a facilitated mediation process whereby the content of agreements emerges from the parties to the conflict themselves, informed by the context within which the conflict is situated. The book presents the core principles and practices of adaptive mediation with empirical evidence from Colombia, Mozambique, The Philippines, and Syria. Cedric de Coning is Research Professor with the Norwegian Institute of International Affairs (NUPI), and Senior Advisor with the African Center for the Constructive Resolution of Disputes (ACCORD). Ako Muto is Executive Senior Research Fellow at the Japan International Cooperation Agency (JICA) Ogata Sadako Research Institute for Peace and Development. Rui Saraiva is Research Fellow at the Japan International Cooperation Agency (JICA) Ogata Sadako Research Institute for Peace and Development.